Leptina e fatores de risco cardiometabólicos em crianças e adolescentes - Gonzaga, Nathalia Costa (2012)
Objective: Analyze the concentration of leptin in children and adolescents and the relationship with cardiometabolic risk factors and metabolic syndrome (MS). Material and methods: The article 1 is systematic review of the literature from BVS, SciELO, PubMed and Scopus databases from 2001 to june 2011. The following descriptors were searched: leptin AND ("metabolic syndrome" OR "syndrome X") AND "cardiovascular diseases. The article 2 is a cross-sectional study including 200 children and adolescents treated at the Centro de Obesidade Infantil in Campina Grande-PB, from April/2009 to March/2010. It were utilized One Way ANOVA, Pos Hoc Bonferroni and linear correlation test of Pearson. The analyses were performed with SPSS version 17.0, considering the significance level of 5%. Results: In review, the leptin was associated to several cardiometabolic risk factors in children and youth age group, especially overweight, hypertriglyceridemy and insulin resistance. In article 2, the mean of leptin in the sample was 22.98 ± 10.8 ng / mL. Leptin was associated with female sex, adolescence, increased waist circunference, high systolic blood pressure, elevated TG, hyperinsulinemia, insulin resistance and metabolic syndrome. In female sex and teenager age range, the average value of leptin was associated with a greater number of factors. Conclusion: The leptin was associated with multiple cardiometabolic risk factors, such as increased waist circunference and insulin resistance, and MS. This relationship differed according to sex and age, with the highest number of associations in girls and adolescents.